Analysis Of Government Regulation Number 12 Of 2021 Regarding PPJB Requirements For Implementation In Indonesian Property Companies - Yetmiaty, Yetmiaty (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This research aims to analyze government regulation number 12 of 2021 regarding PPJB requirements for implementation in property companies in Indonesia. This research method uses an empirical normative legal approach. The results of this research show that the implementation of Government Regulation number 12 of 2021 concerning PPJB system requirements is not very effective when applied to Indonesian Property Companies, especially if Property Companies or Development Actors use the Pre Project Selling concept, where in this concept, development actors can carry out sales or marketing before the property product is built or the licensing requirements have not been met, which results in Article 22 paragraph (5) regarding the PPJB system requirements not being able to comply with practices that occur in the property business world in Indonesia.